PELATIHAN DAN PENDAMPINGAN PENGGUNAAN MEDIA SCHOOLOGY UNTUK PEMBELAJARAN DARING DI ERA PASCA PANDEMI COVID 19 BAGI GURU – GURU DI SMP SATAP N 3 SUKASADA - Ketut Sedana Arta; Desak Made Oka Purnawati; I Wayan Putra Yasa; Raden Ahmad Ginajar Purnawibawa (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
The main objectives of this activity are: (1) Improving the professional development of teachers in the context of utilizing LMS (Schoology) media as online learning media (2) Improving the ability of teachers to compile and present learning materials and evaluations in LMS (Schoology) (3 ) Improving student learning outcomes by using the LMS (Schoology) application. The results of the activity showed that the teachers at SMP Negeri One Roof 3 Sukasada they did not have sources of information related to LMS (Learning Management System) media, especially schoology so that there was no attempt to update the online learning system, and only focused on using social media Whatshap; (2) teachers at SMP Negeri 3 Sukasada One Roof have done online learning but it has not been done optimally, this happens because most teachers use social media applications such as whatshaap and google classroom, and do not provide space for students to learn interactively; (3) most of the teachers complained about online learning because students had decreased interest in learning, this can be seen. Most of the students were late or did not submit their assignments for various reasons such as not having cellphones, damaged cellphones and network problems; (4) teachers at SMP SATAP Negeri 3 Sukasada have never received training on Learning Management Systems (LMS), such as Schoology, so they do not know the advantages or disadvantages of the schoology